Ag-loaded MOFs modified TiO nanorod conductive glass electrode and preparation process thereof
Modifying the TiO2 nanorod conductive glass electrode by Ag-loaded MOFs, the problem of low efficiency and high cost of removing high concentration of norfloxacin antibiotic wastewater in water in the prior art is solved, and the efficient degradation of norfloxacin at a lower bias voltage is achieved, and the electrode material has good stability and durability.
Patent Information
- Application Number
- CN202411818092.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art has problems of low efficiency, high cost and poor heat resistance of materials when removing high concentrations of norfloxacin antibiotic wastewater in water. Especially in the field of photoelectro-catalysis, the band gap width of traditional semiconductor materials is large and the photogenerated electron-hole pairs are rapidly recombined, resulting in extremely low utilization efficiency.
The TiO2 nanorod conductive glass electrode was modified by Ag-loaded MOFs, and TiO2 nanorods were synthesized by hydrothermal method, and Fe and Ti M'MOFs were prepared by solvent-thermal reaction. Ag⁺ was reduced to Ag⁰ through adsorption-ultraviolet light reduction process and modified on the electrode surface.
It achieves efficient degradation of norfloxacin at a lower bias voltage, with a degradation rate of up to 70.62%, while reducing the energy consumption of the reaction system. The electrode material has good stability and durability.
Smart Images

Figure CN119565682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical degradation of antibiotic wastewater, and in particular to an Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode and a preparation process thereof. Background Art
[0002] Application field: The present invention is applied to electrochemical degradation of antibiotic wastewater to remove high-concentration norfloxacin antibiotic wastewater.
[0003] Antibiotics are substances produced by microbial metabolism or artificially synthesized or semi-artificially synthesized, which can effectively prevent other cells from performing biological functions. According to the chemical structure of antibiotics, they can usually be divided into the following seven categories: β-lactam antibiotics, macrolide antibiotics, aminoglycoside antibiotics, chloramphenicol antibiotics, quinolone antibiotics, sulfonamide antibiotics and tetracycline antibiotics. Among them, norfloxacin belongs to quinolone antibiotics, which is one of the typical representatives of antibiotics at present. Due to its good antibacterial effect, it has been widely used since its birth. However, due to its difficult degradation and stable chemical properties, the water environment in the world today is seriously polluted, and antibiotics have been detected in Antarctic seawater. Research and exploration of an efficient and green method for removing antibiotic wastewater has become one of the urgent issues facing the current water environment safety.
[0004] Existing technologies: For the treatment of antibiotic wastewater, current degradation technologies include At present, there are several methods for removing antibiotics from water, including adsorption, Fenton oxidation, biochemical method, and electrochemical oxidation. However, the physical adsorption method mainly relies on the advantage of the large specific surface area of the material itself, and performs adsorption enrichment without changing the physical properties. The pollutants are not truly removed, and there are also problems such as adsorption saturation and adsorbent regeneration. The Fenton method has a strong oxidation ability and is particularly suitable for organic wastewater that is difficult to biodegrade or difficult to be oxidized by general chemical oxidation. However, a large amount of iron-containing sludge will be produced later, and the high treatment cost limits its application. The biochemical method has a stable treatment effect and can adapt to a variety of water bodies and sewage. However, since microorganisms are more demanding on the growth environment, they need to be in an environment with suitable temperature, oxygen, pH value, etc. At the same time, the construction cost is high and the area occupied is large. The electrochemical oxidation method does not require the addition of oxidants, has strong oxidation ability, and has a fast reaction speed, becoming the best way to provide industrial applications. Among them, the traditional photocatalytic method has problems such as low separation efficiency and rapid recombination of electron-hole pairs. If an electric field is applied, it helps to export electrons in time, thereby improving the photocatalytic performance.
[0005] Photoelectrocatalysis has become a research hotspot for efficient and rapid reactions due to its advantages such as being green and environmentally friendly, mild reaction conditions, fast reaction speed, and low reaction energy consumption. The current mainstream reaction directions include water decomposition to produce hydrogen, carbon dioxide reduction, and photoelectrocatalytic degradation of pollutants. Among them, the degradation of pollutants means that in the photoelectrocatalytic reaction, the electrons and holes on the surface of the catalyst will promote the decomposition of pollutants in the water, such as organic dyes, antibiotic residues, pesticide residues, etc., thereby achieving the purpose of environmental purification. Therefore, the synthesis of electrodes with good catalytic performance is the key to the photoelectrocatalytic system. Commonly used semiconductor materials such as TiO2, Cu2O and WO3 have good effects on the degradation of pollutants in wastewater, but because of their large bandgap, they need to be excited under ultraviolet light irradiation, and the photogenerated electron-hole pairs generated recombine quickly, making the utilization efficiency extremely low. For this reason, it is necessary to dope or recombine with other semiconductors. ] The photoresponse range of the catalyst can be expanded by using other methods.
[0006] From a practical point of view, the substrate material is usually selected with low cost and simple synthesis conditions. For the photoelectrocatalytic system, the first thing to consider is the illumination and conductivity of the material. Conductive glass itself is transparent and has low resistance, so conductive glass is a wise choice for the substrate material. The materials of conductive glass mainly include FTO and ITO. Among them, ITO glass is made on the basis of sodium calcium-based or silicon boron-based substrate glass, and is coated with a layer of indium tin oxide film by magnetron sputtering. It has high light transmittance and is suitable for photoelectrocatalytic applications. At the same time, it has good conductivity and low resistivity. However, its cost is relatively high, especially in large-area applications. It has poor heat resistance and is easy to degrade at high temperatures. As a result, its mechanical strength is low and it is fragile.
[0007] FTO conductive glass is fluorine-doped SnO2 conductive glass (SnO2:F), referred to as FTO. Compared with ITO conductive glass, it has lower cost, is suitable for large-scale production, is resistant to high temperatures, and is suitable for high-temperature electrochemical reactions. Therefore, it has higher mechanical strength and is less prone to breakage. Through the above comparisons, FTO conductive glass was selected as the substrate material. Summary of the invention
[0008] The purpose of the present invention is to solve the problems in the background technology and provide an Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode and a preparation process thereof.
[0009] The above technical objectives of the present invention are achieved through the following technical solutions: The Ag@Fe, Ti M'MOFs / TiO2NRs comprises the following preparation steps: Step 1: Preparation of TiO2NRs electrode; Step 1.1: Electrode pretreatment: Methanol, anhydrous ethanol and deionized water are mixed in a volume ratio of 8 mL-12 mL: 8 mL-12 mL: 8 mL-12 mL to form a mixed solution; FTO conductive glass with a size of 1.5 cm-2.5 cm × 1.0 cm-2 cm is ultrasonically cleaned in the mixed solution for 25 min-35 min, then rinsed with deionized water, and finally dried with nitrogen; Step 1.2: Hydrothermal growth: 25mL-35mL of concentrated hydrochloric acid with a concentration range of 36.5%~38.0%wt and 25mL-35mL of deionized water are measured, mixed in a polytetrafluoroethylene liner and stirred at room temperature for 10min-20min; 0.6mL-1mL of tetrabutyl titanate TBT solution is measured and slowly added dropwise to the continuously stirred concentrated hydrochloric acid solution, and stirred at room temperature for 25min-35min to form a lining solution; the FTO conductive glass is placed in the lining solution with the conductive surface facing the container wall and at an angle of 40°-50° with the bottom of the lining, and the lining is sealed; finally, the lining is placed in a reactor, heated at 160℃-200℃ in a forced air drying oven for 4h-8h, and cooled naturally; Step 1.3: Muffle furnace calcination annealing: The substrate is rinsed alternately with deionized water and anhydrous ethanol three times in sequence, and blown dry with nitrogen to obtain TiO2 nanorods; the TiO2 nanorods are placed in a muffle furnace, annealed at room temperature at a heating rate of 1.5℃ / min-2.5℃ / min in an air atmosphere at 420℃-480℃ for 1.5h-2.5h, and naturally cooled to obtain TiO2NRs, wherein the TiO2 nanorod structure size is 60-80nm; As a preference: In the electrode pretreatment stage, methanol, anhydrous ethanol and deionized water are mixed in a specific volume ratio of 8mL-12mL:8mL-12mL:8mL-12mL to clean impurities in FTO conductive glass; methanol can dissolve oil and grease impurities on the glass surface because the polar groups in its molecular structure have affinity for oil, which can disassemble and disperse the oil and weaken its adhesion to the substrate; anhydrous ethanol is volatile and can accelerate the removal of residual organic matter, and can reduce surface tension and help impurities desorb; deionized water washes alcohol and water-soluble impurities to prevent them from interfering with the subsequent growth of nanorods, providing a pure substrate for the growth of nanorods and ensuring stable and consistent electrode performance; The duration of ultrasonic cleaning is set to 25min-35min; the ultrasonic time period is determined according to the characteristics of the impurities and the adhesion, and most impurities can be shaken off in 30min; ultrasonic high-frequency vibration destroys the adhesion between impurities and the substrate; rinsing is to remove residual cleaning agents, because it will change the chemical environment of the substrate and interfere with the chemical process of nanorod growth; nitrogen blowing eliminates the influence of residual water stains, which can cause fluctuations in the electrical properties of the substrate, such as local short circuits or resistance changes. Blowing can improve the success rate of electrode preparation and ensure that the electrical state of the substrate is good before entering the subsequent process; The FTO conductive glass with a size of 1.5cm-2.5cm×1.0cm-2cm is selected to adapt to the reactor cavity and the heating field distribution; in the reactor, this size ensures uniform heat and mass transfer in the hydrothermal growth and annealing process, and avoids imbalance in heat and mass transfer caused by size deviation; if the glass size is too large, there will be uneven heat and mass transfer areas in the reactor, causing uneven growth of nanorods; if the size is too small, the heat and mass transfer efficiency will be reduced, resulting in insufficient growth power of nanorods; the adaptive size ensures that the various regions of the electrode respond synergistically in the photoelectrocatalytic reaction, improves the catalytic efficiency, and enhances the competitiveness of electrode performance; Measure 25mL-35mL of 36.5%-38.0%wt concentrated hydrochloric acid and an equal amount of deionized water to create an ideal acid-base microenvironment for the hydrolysis of tetra-n-butyl titanate; at this concentration, the hydrogen ion concentration is moderate, and the hydrolysis rate is precisely regulated to precisely control the hydrolysis of tetra-n-butyl titanate, so that the generated TiO2 particle size is uniform and orderly distributed, ensuring that the size of the generated nanorods is precisely controlled at 60-80 nm; concentration fluctuations will destroy the reaction balance, resulting in uncontrolled particle size distribution, disordered nanorod growth, and decreased electrode performance; 0.6mL-1mL of tetrabutyl titanate TBT solution is slowly added drop by drop into the concentrated hydrochloric acid solution and stirred to ensure the uniformity of hydrolysis. If the drop is too slow, impurities are easily introduced, which damages the chemical stability of the electrode and the light absorption conversion efficiency. If the drop is too fast, local hydrolysis will be out of control and agglomeration will grow, which will destroy the stability of the precursor sol system and affect the electrode performance. A stable precursor sol system is constructed with an appropriate drop rate, and the precursor is fully reacted after a specific stirring time and temperature, thereby enhancing the chemical stability of the electrode and the light absorption conversion efficiency. The FTO conductive glass is placed with the conductive surface facing the container wall and at an angle of 40°-50° to the bottom of the inner substrate, following the laws of thermal convection and solute diffusion. This angle constructs a heat and mass transfer path, accelerates the diffusion of reactants to the glass surface, and the heat flow scours obliquely to avoid local overheating, ensuring uniform growth of nanorods. Deviating from this angle, the heat flow distribution is unbalanced, causing uneven growth of nanorods and affecting electrode performance. Maintaining the optimized angle can stabilize the uniformity of nanorod growth, lay the foundation for building a high-quality electrode microstructure, and enhance the stability and durability of the electrode in the photoelectrocatalytic reaction. The substrate is rinsed three times with deionized water and anhydrous ethanol alternately and dried with nitrogen to lay a solid foundation for annealing; alternating rinsing removes substrate impurities and solvent residues, and the residual impurities are thermally decomposed at the high temperature of annealing to pollute the crystal structure; nitrogen drying creates an oxygen-free dry environment to prevent water vapor and oxygen interference during annealing; good substrate conditions help annealing optimize the crystal structure, improve quality, build a high-quality TiO2 nanorod architecture, give the electrode stable performance, improve its ability and durability to degrade pollutants in photoelectrocatalysis, and consolidate the environmental purification defense line; During muffle furnace annealing, the key is to operate the heating rate in the range of 420℃-480℃ at a heating rate of 1.5℃ / min - 2.5℃ / min; heating too fast will cause a large temperature difference between the inside and outside of the substrate material, concentrate thermal stress, cause the nanorods to crack and fall off, damage the electrode microstructure, and reduce performance; heating too slowly can reduce thermal stress, but it will cause impurities to diffuse and contaminate the crystal, reducing electrode performance; precise control of the heating rate can balance thermal stress and impurity diffusion, protect the integrity of the nanorod structure and excellent performance, and stabilize the core structure of the electrode in photoelectrocatalytic degradation of pollutants; FTO conductive glass: FTO, or fluorine-doped tin oxide SnO2:F conductive glass, is a transparent conductive material in which fluorine is doped in tin oxide SnO2; it has low resistance, good chemical stability, high temperature resistance and high mechanical strength. It is often used as a substrate material in fields such as photoelectrocatalysis, providing conductive support and stable carriers for electrode reactions, ensuring effective transmission and collection of electrons, and promoting the smooth progress of photoelectrochemical reactions; TiO2 nanorods TiO2NRs: TiO2 is titanium dioxide, and nanorods are nanostructures with a rod-like microscopic morphology. TiO2 nanorods have a large specific surface area and unique optical and electrical properties. They can provide abundant reactive sites, enhance light absorption and carrier transport, and improve the efficiency of photocatalytic degradation of pollutants in photocatalytic reactions. They play an important role as a key active component in electrode systems. MOFs: Metal-organic framework compounds are porous crystalline materials formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. They are characterized by high porosity, large specific surface area, strong structural and functional designability, and can accurately control pore size, topological structure and chemical properties according to different metal nodes and organic ligands. They are widely used in gas adsorption separation, catalysis, sensing and other fields. In this article, the electrode system can increase the specific surface area and the number of active sites of the electrode, optimize the mass transfer process, and enhance the photoelectrocatalytic performance. Hydrothermal growth: A synthetic method in which water is used as a solvent in a closed high-pressure reactor to promote the dissolution of substances, chemical reactions and crystal growth in a high-temperature and high-pressure environment; in this process, high temperature and high pressure can increase the solubility and activity of reactants, accelerate ion diffusion and migration, and promote the formation and growth of crystal nuclei. By precisely controlling parameters such as temperature, pressure, reaction time and precursor concentration, materials with specific morphology, size and crystal structure can be obtained. In the present invention, it is used to prepare TiO2 nanorods and MOFs to construct an active layer for the electrode; Muffle furnace calcination annealing: Muffle furnace is a high-temperature heating equipment; calcination refers to heating materials at high temperatures to change their physical and chemical properties, such as removing impurities, improving crystallinity, changing crystal structure or adjusting material porosity; annealing is heating the material to a specific temperature range and then slowly cooling it to eliminate internal stress, optimize crystal structure, and enhance material stability and mechanical properties; the present invention sequentially calcines and anneals TiO2 nanorods, improves crystal quality, removes residual organic matter and impurities through calcination, and anneals to relieve thermal stress, stabilize crystal structure, and ensure nanorod quality and electrode performance stability; Hydrolysis: Hydrolysis is a chemical reaction of a compound with water where it splits into two parts, one of which combines with hydrogen protons to form a new compound.
[0010] Step 2: Preparation of Fe, Ti M'MOFs / TiO2NRs electrodes: Step 2.1: Solvothermal reaction: 4.0mmol-8.0mmol of 2-aminoterephthalic acid NH2-BDC was dissolved in 20mL-30mL N,N-dimethylformamide DMF, stirred at room temperature for 15min-25min, then 20mL-30mL of methanol and 2.0-3.5mmol of FeCl3・6H2O were added in sequence, and 1.5mmol-2.5mmol of tetrabutyl titanate TBT was slowly added dropwise under magnetic stirring, stirred at room temperature for 25min-35min, then the polytetrafluoroethylene liner was transferred to a stainless steel reactor, and heated at 120℃-180℃ in a forced air drying oven for 40h-56h, and then cooled naturally; Step 2.2: vacuum drying: the material of step 2.1 is washed alternately with methanol and DMF three times, and vacuum dried at 55°C-65°C for 3h-5h to obtain Fe, Ti M'MOFs / TiO2NRs; As a preferred embodiment: 4.0mmol-8.0mmol of 2-aminoterephthalic acid NH2-BDC is dissolved in 20mL-30mL N,N-dimethylformamide DMF. The concentration setting is the core factor that determines the success or failure of MOFs growth. When the concentration is low, there are few nucleation sites and lack of growth power, and MOFs nucleation growth is slow, crystallinity is low, and crystal structure is poor. When the concentration is high, the molecules aggregate and agglomerate and impurity wrap, which destroys the purity and regularity of the crystal and affects the electrode performance. Add 20mL-30mL methanol and 2.0-3.5mmol FeCl3・6H2O. Methanol helps dissolve the precursor molecules, preventing local uneven concentration and adverse effects, and improving molecular activity. FeCl3・6H2O provides metal nodes to build the MOFs skeleton, ensuring electrode adsorption and catalytic performance. The slow dropwise addition of tetrabutyl titanate TBT is the key to controlling the structure of MOFs; uneven addition leads to disordered hydrolysis, product agglomeration and structural defects, damage to specific surface area, pore structure and active sites, weakening electrode performance and pollutant degradation efficiency; the hydrothermal reaction lasts for 40h-56h at 120℃-180℃. According to the characteristics of MOFs, too high temperature leads to crystal collapse and decomposition, while too low temperature leads to weak reaction kinetics and slow crystallization; too short a time leads to incomplete crystal growth, while too long a time leads to easy contamination of impurities, high energy consumption and low efficiency; The core step is to wash the MOFs three times alternately with methanol and DMF. Methanol can efficiently elute physically adsorbed impurities and unreacted monomers, while DMF can remove deep impurities and stabilize the MOFs structure, laying the foundation for subsequent vacuum drying to prevent impurities from interfering with the drying process and causing structural collapse or performance degradation. Vacuum drying is performed at 55-65°C for 3-5 hours. High-temperature drying causes structural collapse, pore deformation, and a drop in performance indicators. Mild drying stabilizes the structure and preserves the pores, protecting the microscopic properties, and providing stable MOFs materials for the electrode, ensuring its long-term and efficient purification of pollutants.
[0011] 2-Aminoterephthalic acid: An organic compound containing amino -NH2 and carboxyl -COOH functional groups; used as an organic ligand to bind metal ions such as Fe³⁺, Ti, etc. in the preparation of MOFs. 4 ⁺, etc., self-assemble to form the skeleton structure of MOFs through coordination bonds. Its structure and properties affect the key properties of MOFs, such as topological structure, pore characteristics and chemical stability. It is one of the core building blocks for constructing MOFs materials. N,N-dimethylformamide (DMF): A commonly used organic solvent with a high boiling point, strong polarity and good solubility, capable of dissolving many organic and inorganic compounds. In the preparation of MOFs, it is used as a solvent to dissolve 2-aminoterephthalic acid NH2-BDC, providing a medium environment for the uniform dispersion of precursor molecules, ensuring full contact and reaction between metal ions and organic ligands, and promoting the nucleation and growth of MOFs; its polarity and solvation ability affect the reaction rate and product crystallization process, and are crucial to the formation of MOFs microstructure; FeCl3・6H2O: Ferric chloride hexahydrate, a chloride salt compound of iron, acts as a metal source in MOF synthesis; the iron ion Fe³⁺ can coordinate with organic ligands, such as 2-aminoterephthalic acid NH2-BDC, to contribute metal nodes and participate in the construction of the MOFs crystal framework structure, determining the metal center environment, charge distribution and electronic structure characteristics of MOFs, thereby significantly affecting the adsorption, catalytic, electrical and other performances of MOFs and derived electrode materials, and giving the electrode the ability to specifically adsorb and catalytically degrade target pollutants; Tetrabutyl titanate TBT: a metal organic compound with active chemical properties, which is easily hydrolyzed and condensed in a hydrothermal reaction system; its hydrolysis product is a titanium-containing hydroxyl compound, which is a precursor substance for forming TiO2 nanostructures or participating in the construction of titanium-based structural units in MOFs; the hydrolysis rate and uniformity are controlled by slow dropwise addition to ensure uniform dispersion and condensation of the hydrolysis product, avoid problems such as agglomeration and defects caused by local uneven concentration, and accurately control the microstructure and performance of the obtained material, which is indispensable for the preparation of high-quality Fe, Ti M'MOFs / TiO2NRs electrodes; Solvothermal reaction: a synthetic technology that uses organic matter as solvent in a closed high-pressure container and utilizes high temperature and high pressure conditions to promote the dissolution of reactants, chemical reactions and crystal growth; the invention is used to synthesize Fe, Ti M'MOFs / TiO2NRs. The high temperature and high pressure environment enhances the activity and solubility of reactants, accelerates ion diffusion and migration, promotes the formation and growth of MOFs crystal nuclei and structural ordering, and accurately controls parameters such as temperature, time, reactant concentration and precursor addition order to achieve precise control of MOFs crystal structure, morphology, particle size and pore structure, laying a microstructural foundation for the preparation of high-performance electrode materials; Vacuum drying: a method of drying materials under reduced pressure; by reducing the ambient pressure and the boiling point of the solvent, the solvent is quickly evaporated and removed at low temperature, thus avoiding damage to the material structure caused by high-temperature drying. In the present invention, the prepared MOFs material is vacuum dried at 55°C-65°C for 3h-5h to prevent the high temperature from causing the MOFs structure to collapse and the pores to deform, thereby maintaining its high specific surface area, regular pore structure and good crystal structure, ensuring that the MOFs material can stably perform the adsorption, mass transfer and catalytic functions in electrode applications, and guaranteeing the long-term and efficient performance of the electrode in purifying pollutants; Step 3: Preparation of Ag@Fe, Ti M'MOFs / TiO2NRs electrodes: Step 3.1: Adsorption-UV reduction: Add the M'MOFs / TiO2NRs electrode to a AgNO3 ethanol solution prepared by mixing 20mL-30mL deionized water and 20mL-30mL anhydrous ethanol, ultrasonically accelerate dissolution, and magnetically stir for 25min-35min. The AgNO3 concentration is 0.1-0.5mol / L. Pour the AgNO3 ethanol solution into a culture dish containing M'MOFs / TiO2NRs / FTO conductive glass, and let it stand in a dark environment for 25min-35min to allow Ag⁺ to adsorb on the surface of M'MOFs / TiO2NRs. Then irradiate with UV light for 1.5h-2.5h to reduce Ag⁺ to Ag. 0 ; Finally, after washing with deionized water and anhydrous ethanol alternately for three times, the Ag@Fe, Ti M'MOFs / TiO2NRs electrode was obtained by vacuum drying at 55℃-65℃ for 3h-5h.
[0012] As a preference, there are reasons for selecting 20mL-30mL deionized water and 20mL-30mL anhydrous ethanol to prepare the AgNO3 ethanol solution; anhydrous ethanol constructs an organic environment to help AgNO3 disperse and enhance affinity with M'MOFs / TiO2NRs to promote adsorption, because the molecular characteristics of ethanol can interact with the molecules of the two; deionized water adjusts the polarity and viscosity of the solution to stabilize the system and prevent concentration fluctuations, ensuring that AgNO3 is evenly distributed and the reaction is stable; the key AgNO3 concentration is 0.1-0.5mol / L. If the concentration is too low, the amount of adsorbed and reduced Ag is small and it is difficult to achieve the expected performance; if the concentration is too high, ion aggregation will cause agglomeration and precipitation to block the electrode pores, reducing activity and stability.
[0013] Ultrasound accelerated dissolution works in tandem with magnetic stirring for 25min-35min. Ultrasound uses high-frequency vibration to break up agglomerations and promote dissolution and diffusion, which can interfere with the solution microstructure and help solute dispersion. Stirring keeps the solution uniform, allowing Ag⁺ to contact the electrode for adsorption, so that the solution components are evenly distributed and the ions fully contact the active sites. The solution is placed in the dark for 25min-35min to reach adsorption equilibrium. If the time is too short, the adsorption will be insufficient because Ag⁺ is not sufficiently attached. If the time is too long, the risk of impurity adsorption will increase, and the impurities will have more time to contact the electrode. This process depends on the diffusion adsorption kinetics of the substance. Time affects the adsorption equilibrium state and the amount of impurity adsorption. Precise control ensures efficient adsorption of Ag⁺ and avoids interference from impurities.
[0014] Wash the electrode three times with deionized water and anhydrous ethanol alternately to maintain electrode performance; first use deionized water to wash away water-soluble impurities and unreacted Ag⁺, and use the water solubility characteristics to remove impurity ions; use anhydrous ethanol to remove organic impurities and weakly adsorbed substances, and purify according to its ability to dissolve and desorb organic matter; the last two times are used to consolidate and prevent impurity residues from affecting Ag deposition and electrode performance. Impurities hinder Ag deposition at active sites, change surface properties, reduce electron transfer efficiency and catalytic selectivity, and multiple washings ensure continuous purification; vacuum drying at 55℃-65℃ for 3h-5h stabilizes the electrode microstructure. High temperature causes Ag to sinter and agglomerate, and MOFs to collapse pores and damage performance. This mild condition slowly removes the solvent, maintains the complete microscopic morphology of the electrode, stabilizes the specific surface area and porosity, and maintains the structural basis and performance advantages of the electrode in a complex system for efficient degradation of pollutants; AgNO3 ethanol solution: a solution prepared by dissolving silver nitrate AgNO3 in a mixed solvent of ethanol and deionized water; silver nitrate is the source of silver ions Ag⁺. When preparing Ag@Fe, Ti M'MOFs / TiO2NRs electrodes, silver ions are reduced to elemental silver Ag on the surface of MOFs / TiO2NRs through the adsorption-ultraviolet light reduction process. 0 , thereby modifying the electrode and improving the electrode performance, such as enhancing the photoelectrocatalytic activity and improving the charge transfer performance; Ultrasonic accelerated dissolution: A technical means of using the high-frequency vibration and cavitation effect generated by the propagation of ultrasound in the solution to achieve rapid dissolution of substances; the high-frequency vibration of ultrasound causes the solution molecules to move violently, destroying the solute agglomeration structure; the instantaneous high-temperature and high-pressure microenvironment generated by the cavitation effect promotes the interaction between the solute molecules and the solvent molecules, accelerates the dissociation and diffusion of the solute, increases the contact area between the solute and the solvent, and increases the dissolution rate. In the process of preparing the electrode, the solute is ensured to be evenly dispersed, the uniformity and stability of the reaction system are improved, and a good foundation is laid for subsequent reactions; Magnetic stirring: A method of mixing and stirring a solution by driving a stirrer in a solution with the help of magnetic force. The stirrer rotates at a constant speed under the action of magnetic force to fully mix the various parts of the solution, avoid solute precipitation and local uneven concentration, ensure uniform distribution of solution components, and fully contact the reaction materials, which is conducive to the smooth progress of chemical reactions, improves reaction efficiency and product uniformity, and ensures that Ag⁺ is fully in contact with the active sites on the electrode surface during electrode preparation, improves adsorption effect and reaction consistency, and enhances electrode performance uniformity and repeatability; Adsorption equilibrium: Under certain temperature and pressure, the adsorption and desorption rates of adsorbents, such as Ag⁺, on the surface of adsorbent M'MOFs / TiO2NRs are equal in a dynamic equilibrium state; when adsorption equilibrium is reached, the adsorption amount no longer changes with time, and it is affected by factors such as adsorbate concentration, adsorbent properties, temperature, and contact time; in this paper, Ag⁺ was allowed to reach adsorption equilibrium on the electrode surface by standing in the dark. Accurately controlling the standing time is of great significance to ensure sufficient adsorption, avoid excessive adsorption of impurities, and optimize electrode performance, because the adsorption amount affects the amount of silver loaded on the active sites of the electrode, which in turn determines the electrode catalytic activity and selectivity; UV irradiation: The operation of using a UV lamp to emit ultraviolet light to irradiate the solution system; ultraviolet light has high energy, which can stimulate the electronic transition of substances and trigger photochemical reactions; it is used here to reduce Ag⁺ adsorbed on the electrode surface to Ag 0 , silver ion reduction deposition is achieved through photogenerated electron transfer to form a single silver-modified electrode surface, which changes the electronic structure of the electrode surface, increases active sites and conductivity, and improves the electrode photoelectrocatalytic performance. The irradiation time and intensity are precisely controlled according to the Ag⁺ concentration and electrode material properties to prevent incomplete reduction or excessive damage to the electrode structure.
[0015] In summary, the beneficial effects of the present invention are: 1. The electrode preparation method is simple: The electrode preparation requires fewer reagents, the synthesis conditions are simple, and the production cost is greatly reduced compared to other electrodes; 2. TiO2 nanorods grow firmly: TiO2 nanorods were synthesized by hydrothermal method. In the corresponding SEM images, it can be observed that the nanorods have a dense structure and are neatly arranged. They grow on smooth FTO conductive glass and are very firm, with little chance of the growth material falling off. 3. The applied bias voltage is low: In the photoelectrocatalytic degradation system, the reactor is illuminated by a xenon lamp to simulate visible light, and a mobile power supply is used to apply a bias voltage. At a voltage of 0.5 V, the degradation rate of 10 mg / L of norfloxacin can reach 57.81% within 120 min, saving the energy consumed by the reaction system. At a voltage of 1.0 V, the degradation rate can reach 70.62% in 120 min; 4. High degradation rate of norfloxacin and good electrode stability: Through five consecutive cycles of degradation experiments, the degradation rate of the reaction system was basically maintained at about 70%, and the experiment was easy to operate, indicating that the electrode has strong catalytic performance and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 are SEM images of TiO2NRs (ab), Fe, Ti M'MOFs / TiO2NRs (cd) and Ag@Fe, Ti M'MOFs / TiO2NRs (ef) of the present invention; Figure 2 It is the XRD spectra of TiO2, Fe Ti M'MOFs / TiO2 and Ag@Fe Ti M'MOFs / TiO2 of the present invention; Figure 3 It curves of Ag@Fe, Ti M'MOFs / TiO2NRs, Fe, Ti M'MOFs / TiO2NRs and TiO2NRs of the present invention; Figure 4 It is a degradation diagram of the degradation efficiency of norfloxacin by the Ag@Fe and Ti M'MOFs / TiO2NRs electrodes of the present invention at different voltages; Figure 5 It is a degradation diagram of the degradation efficiency of norfloxacin by the Fe, Ti M'MOFs / TiO2NRs electrodes loaded with Ag and without Ag at the same voltage; Figure 6 It is a graph showing the degradation efficiency of norfloxacin at the same voltage for Ag@Fe, Ti M'MOFs / TiO2NRs electrodes prepared by dropwise addition of tetrabutyl titanate TBT and Ag@Fe, Ti M'MOFs / TiO2NRs electrodes prepared by direct addition of tetrabutyl titanate TBT; Figure 7 This is the synthetic route of the present invention. DETAILED DESCRIPTION
[0017] The following specific embodiments are merely explanations of the present invention and are not limitations of the present invention. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, such modifications are protected by the patent law as long as they are within the scope of the claims of the present invention.
[0018] The present invention will be described in detail below with reference to the accompanying drawings by way of embodiments.
[0019] Example 1
[0020] A preparation process of Ag-grown MOFs conductive glass modified electrode, comprising: Step 1: Preparation of TiO2NRs electrode; Step 1.1: Electrode pretreatment: Methanol, anhydrous ethanol and deionized water were mixed in a volume ratio of 10 mL: 10 mL: 10 mL to form a mixed solution; a FTO conductive glass with a size of 2.0 cm × 1.5 cm was ultrasonically cleaned in the mixed solution for 30 min to remove oily substances on its surface, then rinsed with deionized water, and finally dried with nitrogen; Step 1.2: Hydrothermal growth: 30 mL of concentrated hydrochloric acid with a concentration range of 36.5% to 38.0% wt and 30 mL of deionized water were measured, mixed in a polytetrafluoroethylene liner and stirred at room temperature for 15 min; 0.8 mL of tetrabutyl titanate TBT solution was measured and slowly added dropwise to the continuously stirred concentrated hydrochloric acid solution, and stirred at room temperature for 30 min to form a uniform lining solution; the FTO conductive glass was placed in the lining solution with the conductive surface facing the container wall and at an angle of 45° to the bottom of the lining, and the lining was sealed; finally, the lining was placed in a reactor, heated at 180°C for 6 h in a forced air drying oven, and cooled naturally; Step 1.3: Muffle furnace calcination annealing: The substrate was rinsed alternately with deionized water and anhydrous ethanol three times, and dried with nitrogen to obtain TiO2 nanorods; the TiO2 nanorods were placed in a muffle furnace, annealed at 450°C in an air atmosphere at room temperature at a heating rate of 2°C / min for 2h, and naturally cooled to obtain TiO2NRs; Step 2: Preparation of Fe, Ti M'MOFs / TiO2NRs electrodes: Step 2.1: Solvothermal reaction: 6.0 mmol of 2-aminoterephthalic acid NH2-BDC was dissolved in 25 mL of N,N-dimethylformamide DMF. After stirring at room temperature for 20 minutes, 25 mL of methanol and 2.88 mmol of FeCl3・6H2O were added in sequence. 1.92 mmol of tetrabutyl titanate TBT was slowly added dropwise under magnetic stirring. After stirring at room temperature for 30 minutes, the polytetrafluoroethylene liner was transferred to a stainless steel reactor, and heated at 150°C in a forced air drying oven for 48 hours, and then cooled naturally. Step 2.2: vacuum drying: the material of step 2.1 was washed three times with methanol and DMF alternately to remove impurities remaining on the surface, and vacuum dried at 60° C. for 4 h to obtain Fe, Ti M'MOFs / TiO2NRs; Step 3: Preparation of Ag@Fe, Ti M'MOFs / TiO2NRs electrodes: Step 3.1 Adsorption-UV reduction: Add the M'MOFs / TiO2NRs electrode to a AgNO3 ethanol solution prepared by mixing 25 mL of deionized water and 250 mL of anhydrous ethanol, dissolve it by ultrasound acceleration, and stir it magnetically for 30 min; the AgNO3 solubility is 0.3 mol / L, pour the AgNO3 ethanol solution into a culture dish containing M'MOFs / TiO2NRs / FTO conductive glass, let it stand in the dark for 30 min, allow Ag⁺ to adsorb on the surface of M'MOFs / TiO2NRs, and then irradiate it with UV light for 2 h to reduce Ag⁺ to Ag 0 ; Finally, after washing with deionized water and anhydrous ethanol alternately for three times, the Ag@Fe, Ti M'MOFs / TiO2NRs electrode was obtained by vacuum drying at 60°C for 4 h.
[0021] Example 2
[0022] The difference from the above-mentioned Example 1 is that the TiO2NRs electrode, Fe, Ti M'MOFs / TiO2NRs electrode and Ag@Fe, Ti M'MOFs / TiO2NRs electrode prepared in Example 1 are observed by scanning microscope SEM, as follows Figure 1 As shown: Observe the TiO2NRs electrode, such as Figure 1 (a) and Figure 1 As shown in (b), under SEM, it can be clearly seen that the TiO2 nanorods have a dense structure, are neatly arranged, and are about 60-80 nm in size; Observe Fe, Ti M'MOFs / TiO2NRs electrodes, such as Figure 1 (c) and Figure 1 (d) It is found that a large number of clustered MOFs appear on the top of the TiO2 nanorods after the solvothermal reaction. They are Ti MOFs, and the neatly arranged octahedral structures on the sides are Fe MOFs, which increases the specific surface area of the electrode and is conducive to providing more reactive sites. Observe the Ag@Fe, Ti M'MOFs / TiO2NRs electrodes, such as Figure 1 (e) and Figure 1 (f) After adsorption-UV light reduction, it can be observed that the reduced elemental Ag grows on the surface of the nanorods, presenting a linear structure with a relatively uniform distribution.
[0023] The TiO2NRs electrode, Fe, Ti M'MOFs / TiO2NRs electrode and Ag@Fe, Ti M'MOFs / TiO2NRs electrode prepared in Example 1 were analyzed by X-ray diffraction (XRD) technology, as follows: Figure 2 As shown: Since TiO2 grows on tin oxide glass, the XRD pattern of the TiO2NRs electrode shows obvious SnO2 characteristic peaks, with obvious characteristic peaks appearing near 2θ of 27.3°, 38.6° and 53.9° (JCPDS 21-1276), which are characteristic peaks of rutile phase TiO2, corresponding to the crystal planes (110), (200) and (211), respectively; obvious Ag characteristic diffraction peaks were observed near 2θ of 38.1° and 44.3° (JCPDS 04-0783), corresponding to the crystal plane (111), indicating that Ag was successfully loaded on Fe Ti M'MOFs / TiO2NRs.
[0024] The instantaneous photocurrent-time curve of the TiO2NRs electrode, Fe, Ti M'MOFs / TiO2NRs electrode and Ag@Fe, Ti M'MOFs / TiO2NRs electrode prepared in Example 1 was used to measure the instantaneous photocurrent of each electrode, as follows: Figure 3 As shown: After the growth of TiO2NRs, the current generated by the electrode under visible light irradiation is extremely small; after the solvothermal reaction to form MOFs, the photocurrent intensity increases, which is due to the ultra-large specific surface area and narrower bandgap width of MOFs; finally, after adsorption-ultraviolet light reduction to load Ag, the photocurrent intensity increases significantly, indicating that silver is successfully loaded on the Fe Ti M'MOFs / TiO2NRs photoanode, effectively increasing the photoelectrocatalytic performance.
[0025] Comparative Example 1: Compared with Example 1, the difference is that Fe, Ti M'MOFs / TiO2NRs are not loaded with Ag after preparation, and the other steps and conditions are the same.
[0026] Comparative Example 2: Compared with Example 1, the difference is that 1.92 mmol tetrabutyl titanate TBT is directly added, and the other steps and conditions are the same.
[0027] Application Example 1: The Ag@Fe and Ti M'MOFs / TiO2NRs electrodes prepared in Example 1 were used as working electrodes. During the PEC process, applying a bias voltage can promote the separation of photogenerated electron-hole pairs. The effect of applying a bias potential on the degradation of norfloxacin was studied: a 10 mg / L norfloxacin solution was prepared, 0.1 mol / L Na2SO4 was added thereto, a 300W xenon cold light lamp was used as the light source, visible light irradiation conditions were simulated, and a bias voltage was applied through an external mobile power supply. The bias voltages were set to 0.5 V, 1.0 V, and 1.5 V (vs. Ag / AgCl), respectively, and the reaction was carried out for 2 h at each voltage. The experimental results are as follows Figure 4 As shown, it shows that with the increase of bias voltage, the degradation of the reaction is promoted to a certain extent. At 1.0 V, the degradation rate of Ag@Fe and Ti M'MOFs / TiO2NRs is the best, reaching 70.62%, compared with 57.81% at 0.5 V and 69.85% at 1.5 V. At 1.0 V, the degradation rate of Ag@Fe and Ti M'MOFs / TiO2NRs is the best and the energy consumption is the least.
[0028] Application Example 2: Comparison of the degradation rates of the Ag@Fe, Ti M'MOFs / TiO2NRs electrodes prepared in Example 1 and the Fe, Ti M'MOFs / TiO2NRs without Ag loading prepared in Comparative Example 1: Prepare a 10 mg / L norfloxacin solution, add 0.1 mol / L Na2SO4 to it, use a 300W xenon cold light lamp as the light source, simulate visible light irradiation conditions, and apply a bias voltage through an external mobile power supply. Set the bias voltage to 1.0V (vs. Ag / AgCl), and carry out the reaction for 2h at this voltage. The experimental results are as follows Figure 5 As shown, it shows that at a voltage of 1.0 V, the electrode degradation rate of Fe, Ti M'MOFs / TiO2NRs loaded with Ag can reach 71.34%, while the electrode degradation rate of Fe, Ti M'MOFs / TiO2NRs without Ag loading only reaches 56.38% at a voltage of 1.0 V. Therefore, the degradation rate of the electrode pair of Fe, Ti M'MOFs / TiO2NRs loaded with Ag is greatly improved.
[0029] Application Example 3: Comparison of the degradation rates of the Ag@Fe, Ti M'MOFs / TiO2NRs electrodes prepared in Example 1 and those prepared in Comparative Example 2: Prepare a 10 mg / L norfloxacin solution, add 0.1 mol / L Na2SO4, use a 300W xenon cold light lamp as the light source, simulate visible light irradiation conditions, and apply bias voltage through an external mobile power supply. Set the bias voltage to 1.0V (vs. Ag / AgCl), and react for 2h at this voltage. The experimental results are as follows Figure 5 As shown, it shows that at a voltage of 1.0 V, the electrode degradation rate of Ag@Fe, Ti M'MOFs / TiO2NRs prepared by dropwise addition of tetrabutyl titanate TBT can reach 69.32%, while the electrode degradation rate of Ag@Fe, Ti M'MOFs / TiO2NRs prepared by directly adding tetrabutyl titanate TBT only reaches 49.89% at a voltage of 1.0 V. Therefore, the step of adding tetrabutyl titanate TBT dropwise can greatly improve the degradation rate.
Claims
1. An Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode, characterized in that: The invention comprises an FTO conductive glass substrate, a TiO2 nanorod on the surface of the FTO conductive glass, Fe and Ti M'MOFs / TiO2NRs on the surface of the TiO2 nanorod, and Ag on the surface of the Fe and Ti M'MOFs / TiO2NRs. 0 .
2. The Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 1, characterized in that: The size of the TiO2 nanorod structure is 60-80 nm.
3. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 1, characterized in that: The Ag@Fe, Ti M'MOFs / TiO2NRs comprises the following preparation steps: Step 1: Preparation of TiO2NRs electrode; Step 1.1: Electrode pretreatment: Methanol, anhydrous ethanol and deionized water are mixed in a volume ratio of 8 mL-12 mL: 8 mL-12 mL: 8 mL-12 mL to form a mixed solution; FTO conductive glass with a size of 1.5 cm-2.5 cm × 1.0 cm-2 cm is ultrasonically cleaned in the mixed solution for 25 min-35 min, then rinsed with deionized water, and finally dried with nitrogen; Step 1.2: Hydrothermal growth: 25mL-35mL of concentrated hydrochloric acid with a concentration range of 36.5%~38.0%wt and 25mL-35mL of deionized water are measured, mixed in a polytetrafluoroethylene liner and stirred at room temperature for 10min-20min; 0.6mL-1mL of tetrabutyl titanate TBT solution is measured and slowly added dropwise to the continuously stirred concentrated hydrochloric acid solution, and stirred at room temperature for 25min-35min to form a lining solution; the FTO conductive glass is placed in the lining solution with the conductive surface facing the container wall and at an angle of 40°-50° with the bottom of the lining, and the lining is sealed; finally, the lining is placed in a reactor, heated at 160℃-200℃ in a forced air drying oven for 4h-8h, and cooled naturally; Step 1.3: calcination and annealing in a muffle furnace: the substrate is rinsed alternately with deionized water and anhydrous ethanol three times in sequence, and blown dry with nitrogen to obtain TiO2 nanorods; the TiO2 nanorods are placed in a muffle furnace, annealed at room temperature at a heating rate of 1.5°C / min-2.5°C / min in an air atmosphere at 420°C-480°C for 1.5h-2.5h, and naturally cooled to obtain TiO2NRs; Step 2: Preparation of Fe, Ti M'MOFs / TiO2NRs electrodes: Step 2.1: Solvothermal reaction: 4.0mmol-8.0mmol of 2-aminoterephthalic acid NH2-BDC was dissolved in 20mL-30mL N,N-dimethylformamide DMF, stirred at room temperature for 15min-25min, then 20mL-30mL of methanol and 2.0-3.5mmol of FeCl3・6H2O were added in sequence, and 1.5mmol-2.5mmol of tetrabutyl titanate TBT was slowly added dropwise under magnetic stirring, stirred at room temperature for 25min-35min, then the polytetrafluoroethylene liner was transferred to a stainless steel reactor, and heated at 120℃-180℃ in a forced air drying oven for 40h-56h, and then cooled naturally; Step 2.2: vacuum drying: the material of step 2.1 is washed alternately with methanol and DMF three times, and vacuum dried at 55°C-65°C for 3h-5h to obtain Fe, Ti M'MOFs / TiO2NRs; Step 3: Preparation of Ag@Fe, Ti M'MOFs / TiO2NRs electrodes: Step 3.1: Adsorption-UV reduction: Add the M'MOFs / TiO2NRs electrode to a AgNO3 ethanol solution prepared by mixing 20mL-30mL deionized water and 20mL-30mL anhydrous ethanol, ultrasonically accelerate the dissolution, and magnetically stir for 25min-35min; pour the AgNO3 ethanol solution into a culture dish containing M'MOFs / TiO2NRs / FTO conductive glass, let it stand in a dark environment for 25min-35min, allow Ag⁺ to adsorb on the surface of M'MOFs / TiO2NRs, and then irradiate with UV light for 1.5h-2.5h to reduce Ag⁺ to Ag 0 ; Finally, after washing with deionized water and anhydrous ethanol alternately for three times, the Ag@Fe, Ti M'MOFs / TiO2NRs electrode was obtained by vacuum drying at 55℃-65℃ for 3h-5h.
4. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 3, characterized in that: In the step 1.2, the tetrabutyl titanate TBT solution is added drop by drop slowly.
5. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 3, characterized in that: In the step 2.1, the order of adding the raw materials is to first dissolve the 2-aminoterephthalic acid in the N,N-dimethylformamide and stir, then add the methanol and the FeCl3·6H2O in sequence, and finally slowly add tetrabutyl titanate drop by drop.
6. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 3, characterized in that: In the step 3.1, the AgNO3 concentration in the AgNO3 ethanol solution is 0.1-0.5 mol / L.
7. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 1, characterized in that: The Ag@Fe, Ti M'MOFs / TiO2NRs are applied to electrochemical degradation of antibiotic wastewater.
8. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 7, characterized in that: The antibiotic wastewater is norfloxacin antibiotic wastewater.
9. The preparation process of a Ag-loaded MOFs-modified TiO2 nanorod conductive glass electrode according to claim 7 or 8, characterized in that: During the electrochemical degradation of Ag@Fe, Ti M'MOFs / TiO2NRs, a bias voltage of 0.5-1.5V (vs. Ag / AgCl) was applied, and a 250-350W xenon cold light lamp was used for irradiation.